Identifikasi Rhodamin B pada Eyeshadow dengan Metode Kromatografi Lapis Tipis - Kurniaty, Rina; Rejeki, Dwi Putri; Syarif, Cut Nurlaili (TIN: Terapan Informatika Nusantara, 2024)
Eyeshadow is a decorative cosmetic or makeup that contains color pigments used on the eyelids. Based on BPOM Decree No. 23 of 2019 concerning technical requirements for cosmetic ingredients, the Indonesian government has determined more than 20 hazardous dyes, and Rhodamin B is the most widely used hazardous synthetic dye as a dyes. This study aims to find out the presence of Rhodamin B dye in eyeshadow sold around the Aceh Market and does not have a registration number by BPOM. This research was conducted in the Multifunctional Laboratory of the Faculty of Science and Technology using the Thin Layer Chromatography method. The results of the study showed that the Rf value of the eyeshadow sample with code A was 0.5 while the standard Rf was 0.8, the Rf of the B code sample was 0.53 while the standard Rf was 0.83, the Rf of the C code sample is 0.83 while the standard Rf is 0.83, the D code sample is 0.41 while the standard Rf is 0.78, and the E code sample Rf is 0.5 while the standard Rf is 0.8. Where the code C the Rf value is equal to the Rf value of the Rhodamin B standard is also 0.83, the result is positive if the sample Rf is the same or close to each other with the difference in the price of the standard Rf ≤0.2. Based on the results of the study, it can be concluded that 1 out of 5 eyeshadow samples sold around Pasar Aceh by Thin Layer Chromatography obtained sample C positive for containing the synthetic dye Rhodamin B.